‘Ngopi Skena’: Konstruksi Wacana Skena sebagai Identitas Territorial Coffee Shop Seturan Yogyakarta - Ramadhani, Wanda Alifa (Program Studi Ilmu Komunikasi UII, 2024)
This research focuses on the material dimension of the territorial identity of coffee shops in Seturan through an analysis that considers how discourses and knowledge shape practices, places, and spaces. Territorial identity is shaped by knowledge produced and reproduced by hegemonic discourses. In this research, the coffee shop scene becomes a discourse that produces knowledge in the form of the territorial identity of coffee shops in Seturan. Through statements such as the Seturan coffee shop being the place for the Jogja scene community and the function of coffee shops becoming instruments for seeking validation and social recognition, the researcher conducted a comprehensive analysis through Foucault's discourse analysis. These two statements are closely related to the production of knowledge in the public's minds that the scene is hipster and cool. Ultimately, the production of truth in this research is not a search for right and wrong based on factual aspects and values but rather truth based on social constructions that are historically dependent and produced through discourse and power relations between subjects.